2018
DOI: 10.1620/tjem.244.133
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of ASC, a Proapoptotic Protein, for Determining the Cisplatin Susceptibility of Lung Cancer Cells

Abstract: Primary lung cancer is the most frequent cause of cancer-related deaths worldwide. Cisplatin has been used as a key drug in the treatment for patients with lung cancer; however, most of the patients failed to respond to cisplatin within several months, and the mechanisms underlying the cisplatin resistance have not been fully elucidated. Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is a key adaptor protein in the formation of inflammasomes. ASC is also involved in apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A study has revealed that the activation of NLRP3 inflammasome participates in CHD progress, and down-regulating NLRP3 and its downstream mediators can suppress the inflammatory process of atherosclerosis [13]. ASC is an important adaptor protein in the formation of inflammasomes [14]. There is a study reporting a neuromodulatory effect of NLRP3 and ASC on neonatal hypoxic-ischemic encephalopathy [15].…”
Section: Introductionmentioning
confidence: 99%
“…A study has revealed that the activation of NLRP3 inflammasome participates in CHD progress, and down-regulating NLRP3 and its downstream mediators can suppress the inflammatory process of atherosclerosis [13]. ASC is an important adaptor protein in the formation of inflammasomes [14]. There is a study reporting a neuromodulatory effect of NLRP3 and ASC on neonatal hypoxic-ischemic encephalopathy [15].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, various pyroptosis pathway members, including but not limited to inflammasomes, gasdermins, and various inflammatory cytokines, have been reported to participate in the genesis, proliferation, metastasis, and invasion of pulmonary cancer (63)(64)(65). Depending on the specific contexts, these components play diverse and even sometimes opposing roles in tumor promotion and therapeutic processes.…”
Section: Pyroptosis and Lung Cancermentioning
confidence: 99%
“…ASC negatively modulated the tumorigenesis of fibrosarcoma by activating caspase-9 and inhibiting the nuclear factor-ĸB (NF-ĸB)-related X-linked inhibitor of apoptosis protein (XIAP) [104]. ASC inhibited the proliferation, motility and invasion of lung cancer cells through downregulation of Bcl-2 and phospho-Src [105]. It has been reported that the apoptosis sponsor caspase-8 also functions as an enhancer of cancer cell migration by phosphorylation via Src [106].…”
Section: The Role Of Inflammasomes In Cancermentioning
confidence: 99%